FERTIDIF: software para la planificación de fertilización agrícola basado en optimización lineal con costos difusos - Niquin-Alayo, Esmelin (2018)
The concepts of fuzzy sets theory for the mathematical modelling of fertilization farmland problems, considering fuzzy costs, are used. With support of programming languages and computer tools, a software called FERTIDIF to contribute in making decisions about the utilization of fertilizer and nutrients required for a particular crop, has been designed. The fertilization problem has been solvedby means of the adaptation of methodologies of solution proposed by Lai-Hwang and Leberling; methodologies transforming a fuzzy problem with fuzzy cost into a multi-objective optimization problem and solved easily by using the FERTIDIF software, providing to the agricultural fertilization specialists to take decisions about the amounts of fertilizer as well as to determine the minimum cost of the fertilization process for a given crop.